High-resolution calibration of seismically-induced lacustrine deposits with historical earthquake data in the Eastern Alps (Carinthia, Austria). (15th May 2022) - Daxer, Christoph; Ortler, Marcel; Fabbri, Stefano C.; Hilbe, Michael; Hajdas, Irka; Dubois, Nathalie; Piechl, Thomas; Hammerl, Christa; Strasser, Michael; Moernaut, Jasper
Abstract: Lake sediments are increasingly used to reconstruct recurrence intervals of large earthquakes - a prerequisite for the establishment of accurate seismic hazard models - because they can record strong seismic shaking as mass-transport deposits (MTDs), turbidites or sediment deformations and often reach back several thousands of years. To derive quantitative information on paleo-earthquake size, the sedimentary imprints need to be thoroughly calibrated with independent information on seismic shaking strength. A few calibration studies proposed scaling relationships between the shaking strength of historical earthquakes and the type and size of lacustrine sedimentary imprints. Due to incomprehensive lacustrine mapping or an insufficient record of documented earthquakes, however, rigorous testing of these scaling relationships is lacking. Here, we study the sedimentary infill of the past ∼800 years in Wörthersee and Millstättersee, two large lakes in the Eastern Alps (Carinthia, Austria). These lakes have experienced five well-documented historical earthquakes with local seismic intensities ranging from V – IX (EMS-98 scale). We trace the sedimentary signatures (MTDs and turbidites) of these earthquakes based on a vast dataset of multibeam bathymetry, reflection seismic profiles and numerous precisely dated sediment cores. Seismic intensities as low as V½ are recorded as turbidites originating from deltaic slopes, while hemipelagic slopes can fail from intensities of VI onwards. In Wörthersee, earthquake-recording thresholds are highly dependent on the specific core locations due to local variations in slope characteristics (composition, length, and gradient) and transport distance to the core site. This highlights the potential for establishing multi-threshold paleoseismic records based on multiple coring sites in a single basin. In both lakes, exponential size-scaling relationships are inferred between seismic intensity and i) number or volume of mass-transport deposits and ii) the cumulative thickness of turbidites. Moreover, the relative turbidite presence increases linearly with seismic intensity, confirming the results from a previous study in Chilean lakes. Application of the obtained size-scaling relationships on the first major earthquake documented for Austria (1201 CE) suggests a magnitude of ∼6.4 and an epicentre close to Millstätter See. This demonstrates that lake paleoseismology is a powerful tool to obtain quantitative information on the seismic intensity distribution of paleo-earthquakes. Highlights: Calibration of earthquake imprints in lakes with historical intensity data. Seismic intensity thresholds are site-specific and range from V½ to VIII½. Scaling relationships between landslides/turbidites and seismic intensity exist. Sedimentation rate is a key parameter controlling earthquake sensitivity of lakes.